Arbacia ballenensis sp. nov. (Echinoidea, Arbacioida): A new species reveals diversification of the genus in Central America - Courville, Erwan; Mooi, Rich; Poulin, Elie; Saucede, Thomas (Zootaxa, 2023)
A new species of Arbacia (Echinoidea, Arbacioida), A. ballenensis sp. nov., from the Late Pliocene—Early Pleistocene of Baja California Norte, México, is described from a series of 62 specimens ranging in size from 6 to 20 mm test diameter. It differs from all extant species in the genus by its high number of interambulacral plates, numerous small interambulacral tubercles, and the size of the interambulacral tags at the peristomial edge. This new species yields new evidence concerning the diversification of the genus along the Pacific coast of North America where previously, only one extinct species was described, Arbacia abiquaensis from the Oligocene of Oregon. A. ballenensis sp. nov. is closely related to the recently described Arbacia quyllur from the late Miocene of Chile. Study of the new species in the context of events such as the mid-Pleistocene Transition helps shed light on patterns of extinction and speciation within the genus.